Dynamics and features of transmission clusters of HIV-1 subtypes in the state of São Paulo, Brazil - Pimentel, Victor; Pineda-Peña, Andrea; Sebastião, Cruz S.; de Paula, João L.; Ahagon, Cintia M.; Pingarilho, Marta; Martins, M. Rosário O.; Coelho, Luana P. O.; Matsuda, Elaine M.; Alves, Daniela; Abecasis, Ana B.; Brígido, Luís F. M. (Frontiers in Public Health, 2024)
Background Molecular epidemiology techniques allow us to track the HIV-1 transmission dynamics. Herein, we combined genetic, clinical and epidemiological data collected during routine clinical treatment to evaluate the dynamics and characteristics of transmission clusters of the most prevalent HIV-1 subtypes in the state of São Paulo, Brazil. Methods This was a cross-sectional study conducted with 2,518 persons living with HIV (PLWH) from 53 cities in São Paulo state between Jan 2004 to Feb 2015. The phylogenetic tree of protease/reverse transcriptase (PR/RT) regions was reconstructed by PhyML and ClusterPicker used to infer the transmission clusters based on Shimodaira–Hasegawa (SH) greater than 90% (phylogenetic support) and genetic distance less than 6%. Results Of a total of 2,518 sequences, 2,260 were pure subtypes at the PR/RT region, being B (88%), F1 (8.1%), and C (4%). About 21.2% were naïve with a transmitted drug resistance (TDR) rate of 11.8%. A total of 414 (18.3%) of the sequences clustered. These clusters were less evident in subtype B (17.7%) and F1 (15.1%) than in subtype C (40.2%). Clustered sequences were from PLWH at least 5 years younger than non-clustered among subtypes B (p < 0.001) and C (p = 0.037). Men who have sex with men (MSM) predominated the cluster in subtype B (51%), C (85.7%), and F1 (63.6%; p < 0.05). The TDR rate in clustered patients was 15.4, 13.6, and 3.1% for subtypes B, F1, and C, respectively. Most of the infections in subtypes B (80%), C (64%), and F1 (59%) occurred within the state of São Paulo. The metropolitan area of São Paulo presented a high level of endogenous clustering for subtypes B and C. The São Paulo city had 46% endogenous clusters of subtype C. Conclusion Our findings showed that MSM, antiretroviral therapy in Treatment-Naive (ART-naïve) patients, and HIV1-C, played an important role in the HIV epidemic in the São Paulo state. Further studies in transmission clusters are needed to guide the prevention intervention.